2019
DOI: 10.3390/en12122411
|View full text |Cite
|
Sign up to set email alerts
|

Do Carbon Emissions and Economic Growth Decouple in China? An Empirical Analysis Based on Provincial Panel Data

Abstract: Global warming has emerged as a serious threat to humans and sustainable development. China is under increasing pressure to curb its carbon emissions as the world’s largest emitter of carbon dioxide. By combining the Tapio decoupling model and the environmental Kuznets curve (EKC) framework, this paper explores the relationship between China’s carbon emissions and economic growth. Based on panel data of 29 provinces from 2007 to 2016, this paper quantitatively estimates the nexus of carbon emissions and econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…However, to capture a broader picture there is a need to extend these types of models to other high CO 2 emitting countries because excessive CO 2 generation and its ensuing negative effects on human, animal, and plant wellbeing is a grave danger to the planet, let alone sustainable development [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to capture a broader picture there is a need to extend these types of models to other high CO 2 emitting countries because excessive CO 2 generation and its ensuing negative effects on human, animal, and plant wellbeing is a grave danger to the planet, let alone sustainable development [5].…”
Section: Discussionmentioning
confidence: 99%
“…There is a comprehensive consensus among researchers that the problems of climate change and environmental problems have been caused by human activities [4]. Currently, global warming and its fallout are among severe threats to sustainable development and life itself [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bidirectional causality is found between GW and EMS. Hao et al (2019) examined the relationship between EMS and GW in China for the period of 2007 to 2016. Hao et al found that an EKC relationship exists between EMS and GW.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In recent years there has been a downward trend in energy consumption in European countries, associated with the growing consumption of renewable energy to counteract pollution [1]. According to the European Environment Agency, overall consumption was reduced by more than 10% in the period 2005-2015, mainly as a result of two factors: An increase in energy efficiency, and the implementation of energy policies in countries.…”
Section: Introductionmentioning
confidence: 99%